Incidence of postoperative atrial fibrillation recurrence in patients discharged in sinus rhythm after cardiac surgery: a systematic review and meta-analysis. (17th November 2017) - Lowres, Nicole; Mulcahy, Georgina; Jin, Kai; Gallagher, Robyn; Neubeck, Lis; Freedman, Ben
Abstract: Postoperative atrial fibrillation (POAF) is associated with increased stroke risk and mortality post-discharge. POAF is often considered transient; however, recurrence is likely under-recognized as symptoms are an unreliable guide. Surveillance post-discharge may identify asymptomatic POAF recurrences in patients discharged in sinus rhythm. Therefore, we performed a systematic review and meta-analysis of studies investigating POAF recurrence post-discharge, in patients with new-onset POAF following cardiac surgery who reverted to sinus rhythm prior to discharge. Two independent reviewers searched medical databases, clinical trial registries, reference lists and the Internet. After screening from 6525 studies, 8 studies were identified ( n  = 1157 participants, mean age 66 ± 10 years and 73% men). Monitoring methods included the following: telemetry during twice-daily exercise sessions ( n  = 2), continuous telemetry for 3 weeks ( n  = 1), daily 20-s electrocardiography (ECG) using wearable event recorder ( n  = 1), 30-s single-lead ECG, 4 times/day ( n  = 1) and implanted continuous monitoring ( n  = 2). The incidence rate of POAF recurrence identified through non-invasive monitoring in the first 4 weeks post-discharge was 28.3% [confidence interval (CI) 23.0–33.6%]; recurring 12 ± 5 days (mean ± SD) post-surgery. The incidence rate identified through implanted continuous monitoring was 61–100% within 2 years. Between 40% and 93% of episodes were asymptomatic. In one small study reporting stroke risk, 8 of 10 patients with recurrence were guideline-indicated (CHA2 DS2 -VASc score ≥2) for oral anticoagulation for stroke prevention. Monitoring for POAF recurrence post-hospital discharge identifies significant numbers of early asymptomatic recurrences in patients at high risk of stroke who may benefit from anticoagulation for stroke prevention. More intense monitoring is more likely to identify POAF recurrence. Future research is required to investigate the prognostic significance of POAF recurrence, especially stroke and mortality risk.